2012
DOI: 10.1029/2011gb004109
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical controls on soil black carbon preservation

Abstract: [1] Black carbon (BC) has long been considered a chemically resistant component of soil organic carbon (SOC). However, there is substantial evidence that the chemistry of most C compounds is less important for long-term storage than is physical protection (e.g., mineral sorption). We explored BC retention in grasslands that lie along a climate gradient that produces strong differences in short range order (SRO) minerals known to drive landscape-scale retention of SOC. We measured soil BC content using 13 C nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 83 publications
(85 reference statements)
4
58
0
Order By: Relevance
“…This suggests that the hydrodynamic transport and depositional mechanism could also be an important factor affecting the occurrence of BC and TOC and their relationships, especially in the open GOT. Actually, this good correlation between BC and bulk OM was not only noticed in the particle phase (e.g., in soil, Glaser and Amelung, 2003;Cusack et al, 2012) but also in the dissolved phase and has been reported worldwide (e.g., Dittmar et al, 2012;Jaffe et al, 2013;Ding et al, 2013Ding et al, , 2015. The close relationship between BC and bulk OM in the dissolved phase could indicate that the release and subsequent sorption and desorption processes of BC are a complex function of environmental factors and particle properties, just as for bulk dissolved OM , which suggests that the mobilization of BC and bulk OM in various matrices is also mechanistically coupled.…”
Section: Relationships Between Bc Toc and Sediment Grain Size And Pomentioning
confidence: 99%
“…This suggests that the hydrodynamic transport and depositional mechanism could also be an important factor affecting the occurrence of BC and TOC and their relationships, especially in the open GOT. Actually, this good correlation between BC and bulk OM was not only noticed in the particle phase (e.g., in soil, Glaser and Amelung, 2003;Cusack et al, 2012) but also in the dissolved phase and has been reported worldwide (e.g., Dittmar et al, 2012;Jaffe et al, 2013;Ding et al, 2013Ding et al, , 2015. The close relationship between BC and bulk OM in the dissolved phase could indicate that the release and subsequent sorption and desorption processes of BC are a complex function of environmental factors and particle properties, just as for bulk dissolved OM , which suggests that the mobilization of BC and bulk OM in various matrices is also mechanistically coupled.…”
Section: Relationships Between Bc Toc and Sediment Grain Size And Pomentioning
confidence: 99%
“…Recent case studies that examined the relationship between DOC and DBC as well as soil BC and soil organic matter (Cusack et al, 2012;Glaser et al, 2003) are consistent with this observation. Because the abundance distribution for DOC and DBC concentrations were not normally distributed, I grouped the samples according to their DOC concentrations into 15 groups for further statistical analysis (Fig.…”
Section: Estimation Of Global Riverine Dbc Flux To the Oceanssupporting
confidence: 52%
“…Additional reasons could be differences in the soil and DOM characteristics among the wetlands. Cusack et al (2012) reported a linear correlation between soil organic carbon (SOC) and soil BC, indicating that mineralogical interactions between soil BC and minerals could preserve the BC.…”
Section: Principal Component Analysis Of Bpcas Evergladesmentioning
confidence: 99%
See 2 more Smart Citations